GeoTree: A participatory digital tool for forest landscape restoration in the tropics - Eitzinger, Anton; Feil, Christian; Ekue, Marius; Oduor, Francis; Kettle, Christopher (2024)
Forest landscape restoration (FLR) in the tropics is often undertaken by smallholders and communities whose livelihoods rely on agriculture and forestry. While digital technologies can improve efficiency in FLR efforts, socio-technical barriers often impede the participation of these key actors in the restoration process.